Noncanonical Roles of hα-syn (A53T) in the Pathogenesis of Parkinson’s Disease: Synaptic Pathology and Neuronal Aging - Qing-Jun Wang; An-Di Chen; Hai-Chao Chen; Dong-Xin Wang; Yi-Ting Cai; Jie Yin; Yu-Hong Jing; Li-Ping Gao (Neural Plasticity)
The motor and nonmotor symptoms of PD involve several brain regions. However, whether α-syn pathology originating from the SNc can directly lead to the pathological changes in distant cerebral regions and induce PD-related symptoms remains unclear. Here, AAV9-synapsin-mCherry-human SNCA (A53T) was injected into the unilateral SNc of mice. Motor function and olfactory sensitivity were evaluated. Our results showed that AAV9-synapsin-mCherry-human SNCA was continuously expressed in SNc. The animals showed mild motor and olfactory dysfunction at 7 months after viral injection. The pathology in SNc was characterized by the loss of dopaminergic neurons accompanied by ER stress. In the striatum, hα-syn expression was high, CaMKβ-2 and NR2B expression decreased, and active synapses reduced. In the olfactory bulb, hα-syn expression was high, and aging cells in the mitral layer increased. The results suggested that hα-syn was transported in the striatum and OB along the nerve fibers that originated from the SNc and induced pathological changes in the distant cerebral regions, which contributed to the motor and nonmotor symptoms of PD.